How does Fixation Alignment Affect Surgical Outcomes in Arthrodesis for Thumb Carpometacarpal Osteoarthritis? - Komura, Shingo; Hirakawa, Akihiro; Hirose, Hitoshi; Kawaguchi, Atsushi; Ito, Yoshiki; Akiyama, Haruhiko (Journal of Wrist Surgery, 2024)
Arthrodesis is a traditional surgical procedure for treating thumb carpometacarpal (CMC) osteoarthritis. Previous studies have investigated surgical outcomes, focusing on the fixation technique, bone union rate, and surgical complications but not on the postoperative alignment of the thumb CMC joints. Therefore, we aimed to investigate how thumb fixation alignment affects the surgical outcomes of thumb CMC arthrodesis.Twenty-six patients (28 thumbs) who achieved bone union after arthrodesis with more than 1-year follow-up were retrospectively analyzed. We measured the radial abduction and palmar abduction angles and change in thumb length (Δthumb length) on postoperative radiographs and the first metacarpal rotation angle on postoperative computed tomography. Moreover, we investigated the 1-year clinical outcomes, including the Disabilities of Arm, Shoulder, and Hand (DASH) score, Hand20 questionnaire score, visual analog scale (VAS) score for pain, Δgrip strength, Δpulp pinch, and Δkey pinch strength. The correlation between the postoperative alignment and clinical outcomes was also statistically analyzed.The mean radial abduction, palmar abduction, first metacarpal rotation angles, and Δthumb length were 20.8 degrees, 34.4 degrees, 109.4 degrees, and −1.8 mm, respectively. Radial abduction and palmar abduction angles were positively and negatively correlated with Δgrip strength (r = 0.37 and −0.37), respectively. The first metacarpal rotation angle was positively correlated with the DASH score (r = 0.51), Hand20 score (r = 0.48), and VAS score for pain (r = 0.42). ΔThumb length had no correlation with clinical outcomes at 1-year follow-up.Thumb fixation alignment has an impact on the surgical outcomes of thumb CMC arthrodesis. To obtain a successful outcome, it is important to add slight pronation and avoid excessively small radial abduction and excessively large palmar abduction.
Keywords: thumb carpometacarpal osteoarthritis; arthrodesis; alignment; surgical outcomes